2010
DOI: 10.1186/1743-422x-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza virus monitoring in wintering waterbirds in Iran, 2003-2007

Abstract: BackgroundVirological, molecular and serological studies were carried out to determine the status of infections with avian influenza viruses (AIV) in different species of wild waterbirds in Iran during 2003-2007. Samples were collected from 1146 birds representing 45 different species with the majority of samples originating from ducks, coots and shorebirds. Samples originated from 6 different provinces representative for the 15 most important wintering sites of migratory waterbirds in Iran.ResultsOverall, AIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
41
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 30 publications
6
41
1
3
Order By: Relevance
“…These findings suggest that virological testing alone does not always reflect the dynamics of AIV infection, a finding consistent with other wild bird studies that have included serological testing (4,5,23). Moreover, low rates of viral detection are likely related to the timing of sampling and the narrow window of opportunity to detect virus that is normally excreted for a short duration, or possibly other factors such as preexisting immunity in the flock.…”
Section: Virologysupporting
confidence: 77%
“…These findings suggest that virological testing alone does not always reflect the dynamics of AIV infection, a finding consistent with other wild bird studies that have included serological testing (4,5,23). Moreover, low rates of viral detection are likely related to the timing of sampling and the narrow window of opportunity to detect virus that is normally excreted for a short duration, or possibly other factors such as preexisting immunity in the flock.…”
Section: Virologysupporting
confidence: 77%
“…Antibody prevalence estimates and speciesspecific prevalence reported herein are consistent with trends from West and Central Asia and the Middle East (Fereidouni et al, 2010), with no detectable antibodies in Grey Herons (Ardea cinerea) or Great Cormorants and high prevalence in Anseriformes. The latter is consistent with patterns observed in Europe (Arenas et al, 1990;Astroga et al, 1994;De Marco et al, 2003), and North America (Brown et al, 2010) among wintering waterbirds.…”
supporting
confidence: 84%
“…Migratory birds as a source of incursion cannot be ruled out presently, but it seems unlikely. Fereidouni et al [15] have shown that the H9 lineages circulating in wild birds in Iran are distinguishable from those in poultry.…”
mentioning
confidence: 98%